Which technology to which challenge in democratic governance? An approach using design science research - Anastasiadou, Maria (2021)
Anastasiadou, M., Santos, V., & Montargil, F. (2021). Which technology to which challenge in democratic governance? An approach using design science research. Transforming Government: People, Process and Policy, 15(4), 512-531. https://doi.org/10.1108/TG-03-2020-0045